2020
DOI: 10.1088/1748-9326/abb908
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of socioeconomic and governance conditions in country-level marine aquaculture production

Abstract: Marine aquaculture (i.e. seafood farming in the ocean) has the potential to substantially support growing demand for animal protein. Despite vast amounts of suitable ocean space across the world, marine aquaculture development has been slow and geographically heterogeneous, indicating that factors other than suitable farming conditions are influencing industry growth. Using multivariate techniques, this study explores to what extent certain socioeconomic, governance, and biophysical factors can explain country… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Northern America and Europe exhibited higher rankings for human development, and so while threats from climate change exist, their capacity to withstand and respond to these threats may be greater. This result is consistent with the known importance of socio-economic factors in aquaculture, especially governance and regulation, which influence whether countries engage with mariculture and its sustainable development [49,50]. Using existing platforms of good governance to build momentum for global, regional and local applications to enhance industry or sector-wide transformative capacity could be a way to support industry and communities to move beyond solely coping strategies in response to climate change and engage more easily with adaptive and transformative approaches, which will increase resilience [30].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Northern America and Europe exhibited higher rankings for human development, and so while threats from climate change exist, their capacity to withstand and respond to these threats may be greater. This result is consistent with the known importance of socio-economic factors in aquaculture, especially governance and regulation, which influence whether countries engage with mariculture and its sustainable development [49,50]. Using existing platforms of good governance to build momentum for global, regional and local applications to enhance industry or sector-wide transformative capacity could be a way to support industry and communities to move beyond solely coping strategies in response to climate change and engage more easily with adaptive and transformative approaches, which will increase resilience [30].…”
Section: Resultssupporting
confidence: 84%
“…Regions and countries that are more prepared for or more capable of responding and adapting to the impacts of climate change will have better capacity to implement ongoing strategies in aquaculture production systems, which will reinforce improvements in resilience through positive change in the absorptive, adaptive and transformative capacity of a community [30]. Good governance and investment into infrastructure, knowledge and capacity can support effective, sustainable development [49,50]. We viewed these factors as 'enablers' of this opportunity, and therefore leverage.…”
Section: (C) Indicators Of Leveragementioning
confidence: 99%
“…seed/fingerlings, feed), local demand for farmed products and supportive industry organizations and financing institutions could all be important. 20,27,71 Aspects of governance beyond government policy, including social movements, market-based programmes and public-private partnerships, have enabled or inhibited industry development and expansion in many parts of the world. 72,73 Environmental nongovernmental organizations have played a particularly large role in sustainable seafood governance, leading sustainability initiatives, developing production standards and shaping public attitudes about aquaculture.…”
Section: Looking B E Yond G Overnment Mariculture P Olic Ymentioning
confidence: 99%
“…Research evaluating the temporal patterns of mariculture development worldwide found that the heterogeneity in country‐level mariculture production trajectories is explained in part using indicators such as regulatory quality and governance effectiveness 26 . In another global analysis, regulatory quality and the existence of spatial planning were shown to be associated with higher volumes of mariculture production for some farmed species 27 28 …”
Section: Introductionmentioning
confidence: 99%
“…It is the cultivation (growing, rearing, breeding, and maintenance) and harvesting of algae, aquatic plants, fish, crustaceans, mollusks, and other organisms in varied aquatic environments that include ponds, lakes, rivers, and estuaries [1,2]. Aquaculture has significant socioeconomic value [3][4][5]. The FAO reports that in 2018, the total export value of fish traded internationally was US $ 164 billion [6].…”
Section: Introductionmentioning
confidence: 99%